ANALYSIS OF THE IMPLEMENTATION OF BIOLOGY PRACTICUM AND ITS RELATIONSHIP WITH STUDENT HIGHER ORDER THINKING SKILLS AND LEARNING OUTCOMES - Muhammad Alfaraby; Herbert Sipahutar (Jurnal Pelita Pendidikan, 2023)
This study aims to find out whether the implementation of biology practicum has a relationship with higher-order thinking skills and learning outcomes of class XI IPA students of SMA Negeri 3 Tanjung Balai in the academic year 2021/2022. All students of class XI IPA, totaling 137 students, were used as research samples. The research instrumentswere consisted of a questionnaire (for practicum implementation), an essay test(for higher- order thinking skills), and a multiple choice test(for student learning outcomes). The data were analyzed in a quantitative descriptive manner by presenting the answers of the respondents regarding the research on implementing practices, higher order thinking skills, and student learning outcomes. The results of this study indicate that the implementation of biology practicum is included in the good category with a percentage of 77%. Students' high-order thinking skills in biology learning are included in the good category with a percentage of 78%, and student learning outcomes in biology learning are included in the good category with a percentage of 76%. This also meets the KKM standard (Minimum Completeness Criteria).